Pemodelan Banjir Berdasarkan Pendekatan Hidrometeorologi dan Perubahan Tutupan Lahan di Sub-DAS Distrik Abepura - Finnyalia Napitupulu; Johnson Siallagan; Maklon Warpur (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2025)
Land cover change has a significant impact on the hydrology of watershed areas, including increasing flood risk. This study aims to analyze land cover changes in the Siborgonyi and Acai sub-watersheds between 2013 and 2022 and their impact on flood potential. The methods used include spatial analysis with GIS, flood modeling using HEC-RAS, and Curve Number (CN) calculations to identify changes in soil infiltration capacity. The results show that land cover changes have a substantial effect on the increase in flood risk. The reduction of forest areas and the expansion of built-up land indicate a large-scale conversion of natural vegetation into residential and infrastructure areas. CN values in 2022 increased across most areas, indicating reduced soil infiltration capacity and increased surface runoff. Flood modeling shows that both the extent and depth of inundation significantly increased in 2022, particularly in downstream areas with basin-like topography.